Risky business: Experiential learning, information and communications technology, and risk-taking attitudes in entrepreneurship education. Issue 2 (July 2018) - Bandera, Cesar; Collins, Regina; Passerini, Katia
Abstract: This paper presents two studies examining the effects of technology-supported experiential entrepreneurship education on learners' entrepreneurial intentions and attitudes towards risk. Each study compares students enrolled in three distinct self-selected college entrepreneurship courses that, to different degrees, integrate information and communications technology (ICT) and interactions with entrepreneurs in a business incubator. Study 1 investigates students' pre-existing attitudes towards entrepreneurship and ICT through a survey distributed at the beginning of the semester. Study 2 explores students' perceptions towards entrepreneurship, risk taking, ICT, and the incubator after the course and retrospectively through a second survey. Responses revealed that students' perceptions were sensitive to their initial entrepreneurial intentions and their interactions with incubator entrepreneurs, but only risk tolerance increased significantly across all courses. A predictive model of student attitudes reveals that perceptions of ICT usefulness moderated the relationship between entrepreneurial attitudes and risk. This work helps bridge entrepreneurship education and education technology by constructing and empirically testing a model relating entrepreneurial characteristics and ICT attitudes. It contributes a mechanism to pedagogy theory that educators can use to improve learning outcomes, and presents educators with experiential strategies that impact student attitudes towards taking risks in business start-ups - an elusive goal of entrepreneurship education. Highlights: We examine ICT-supported experiential entrepreneurship education. We develop and test a predictive model of student attitudes and perceptions. Risk tolerance increased significantly in three distinct entrepreneurship courses. Perceived ICT usefulness moderated the link between attitudes and risk tolerance. Changes in risk tolerance measure the effectiveness of entrepreneurship education.